History Analysis, Form of Presentation, and Function Tortor Naposo Nauli Bulung on Batak Mandailing Communities - Dilinar Adlin; Ruth Hertami Dyah Nugrahaningsih (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
Tortor Naposo Nauli Bulung is one of North Sumatra's local dance content, originating from the Mandailing Batak. As a traditional dance, this tortor has binding rules, sourced from the Dalihan Na Tolu kinship system, which illustrates the roles in it such as kahanggi, Mora, and boru children, so that the various movements contain traditional rules and norms that apply and must be obeyed when adhered to to dance it. This article discusses the history, form of presentation, and function of tortors. Theories used to explore history are the progressive-linear theory according to Ibn Khaldun, Djelantik's opinion for the form of presentation, and the theory of function according to Shay. The research method is descriptive qualitative. The results of the study conveyed Tortor Naposo Nauli Bulung became a medium for socializing. This tortor was performed by young people with six or three pairs of dancers. The floor pattern used was only two shapes, namely the horizontal line pattern and the triangle shape. The group of dancers in the front are called 'na gakspi' or 'na isembar', while the group in the back is called 'pangayapi' or 'panyembar'. The basic motions of the Naposo Nauli Bulung tortor are: a) Manyomba tu Raja, b) Markusor (spinning), and c) Singgang (squatting). Naposo Nauli Bulung Tortor contains four functions, namely: as a reflection and legitimacy of the social order, as a vehicle for secular rite expression, dance as social entertainment or recreational activities, and dance as a reflection of aesthetic values.